Impact of Cognitive Restructuring and Token Economy Techniques on Truancy Reduction among Secondary School Students in Lagos State, Nigeria - Sulaiman, Afolasade Airat; Uhuegbu, Stella Ihuoma (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
This study examined the impact of cognitive restructuring and token economy techniques on the reduction of truancy among secondary school students in Lagos State, Nigeria. The study adopted a pre-test, post-test, control group design with a multistage sampling technique as the sampling method. Judgmental sampling technique was used to select two from the six Education Districts in Lagos State, simple random sampling technique was adopted to select six schools; three schools from each of the two Education Districts and 170 truants out of the 216 randomly selected based on the class attendance register completed the study. Truancy Behaviour Questionnaire (TBQ) with a reliability index of .87 was the instrument for the study. Data were analysed and presented with descriptive and ANOVA statistics at .05 level of significance. Findings showed that the two techniques were effective for the reduction of truancy but the token economy technique had a better effect. Sex had no significant effect on the reduction of truancy but females play truants more than males. Based on the findings, the token economy therapy was recommended as an ideal technique for counselling and guiding students against truancy.